2017
DOI: 10.4244/eij-d-17-00279
|View full text |Cite
|
Sign up to set email alerts
|

COOL AMI EU pilot trial: a multicentre, prospective, randomised controlled trial to assess cooling as an adjunctive therapy to percutaneous intervention in patients with acute myocardial infarction

Abstract: Aims: We aimed to investigate the rapid induction of therapeutic hypothermia using the ZOLL Proteus Intravascular Temperature Management System in patients with anterior ST-elevation myocardial infarction (STEMI) without cardiac arrest. Methods and results:A total of 50 patients were randomised; 22 patients (88%; 95% confidence interval [CI]: 69-97%) in the hypothermia group and 23 patients (92%; 95% CI: 74-99) in the control group completed cardiac magnetic resonance imaging at four to six days and 30-day fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(66 citation statements)
references
References 21 publications
3
50
0
11
Order By: Relevance
“…The results in this study reinforce the value of achieving sufficient cooling prior to reperfusion, and support efforts to improve the technology to cool faster and more effectively. To this end, the recently reported COOL AMI EU pilot study, which used a more powerful cooling system in patients with anterior STEMI, showed an absolute 7% (relative 30%) decrease in infarct size in the per protocol population, warranting the value in performing a fully powered randomized control trial to confirm this signal …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The results in this study reinforce the value of achieving sufficient cooling prior to reperfusion, and support efforts to improve the technology to cool faster and more effectively. To this end, the recently reported COOL AMI EU pilot study, which used a more powerful cooling system in patients with anterior STEMI, showed an absolute 7% (relative 30%) decrease in infarct size in the per protocol population, warranting the value in performing a fully powered randomized control trial to confirm this signal …”
Section: Discussionmentioning
confidence: 98%
“…To this end, the recently reported COOL AMI EU pilot study, which used a more powerful cooling system in patients with anterior STEMI, showed an absolute 7% (relative 30%) decrease in infarct size in the per protocol population, warranting the value in performing a fully powered randomized control trial to confirm this signal. 18…”
Section: Challenges To Overcome For Inducing Hypothermia In Stemi Patmentioning
confidence: 99%
“…Еще одним вариантом кардиопротекции является ишемическое коронарное посткондиционирование, суть которого заключается в проведении серии циклических раздуваний баллона в просвете КА непосредственно после имплантации стента и восстановления [28] • Минимально инвазивная стратегия у избранных пациентов (П М) [32,33] • Ишемическое посткондиционирование (П М К) [34,35] • Механическая тромбэктомия (П М) [2] • Эксенатид, лираглутид (П) [36] • Оксид азота (П) [37] • Блокаторы кальциевых каналов (П М) [38] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Прерывистая окклюзия коронарного синуса (П) [40] • Эксенатид, лираглутид (П) [36] • Предсердный натрийуретический пептид (П) [36] • Гипотермия (П) [28] • Аденозин (П М) [39] • Цилостазол (П) [42] Не рекомендовано…”
Section: анализ профилактических и лечебных тактикunclassified
“…There have been no systematic studies on the administration of antipyretics to patients who have suffered myocardial infarction. In contrast, several studies have investigated the induction of therapeutic hypothermia before or during a percutaneous coronary intervention with the aim of limiting infarct size (16,19,20). However, none of these studies has yet demonstrated convincingly that induction of mild hypothermia during a myocardial infarction is of any benefit to the patient (21,22).…”
Section: Post-myocardial Infarction Fevermentioning
confidence: 99%